2019
DOI: 10.1021/acsomega.9b00718
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Nature of Neutral and Charged Two-Photon Absorbing Squaraines for Fluorescence Bioimaging Application

Abstract: The electronic properties of neutral 2,4-bis(4-bis(2-hydroxyethyl) amino-2-hydroxy-6-(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)phenyl)squaraine (1) and charged 2-((3-octadecylbenzothiazol-2(3H)-ylidene)methyl)-3-oxo-4-((3-(4-(pyridinium-1-yl)butyl)benzo-thiazol-3-ium-2-yl)methylene)cyclobut-1-enolate iodide (2) squaraine derivatives were analyzed based on comprehensive linear photophysical, photochemical, nonlinear optical studies (including two-photon absorption (2PA) and femtosecond transient absorption spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…At an early time scale of 100 fs, it shows the broad positive band at ∼500 nm and two negative absorption bands at around 630 and 730 nm. The positive band at ∼500 nm is due to the excited singlet-state absorption (ESA, S n ← S 1 transition) of the compound. , With the increase of delay time, at 900 fs, the negative band at 630 nm shifted to the blue region (600 nm) consistent with the ground-state bleaching (GSB) of the absorption spectra of ABSQ-H , whereas the negative transient absorption band at 730 nm evolved to attain the steady-state emission maximum at 740 nm, corresponding to the stimulated emission (SE). In addition, a formation of peak at around 680 nm was observed.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…At an early time scale of 100 fs, it shows the broad positive band at ∼500 nm and two negative absorption bands at around 630 and 730 nm. The positive band at ∼500 nm is due to the excited singlet-state absorption (ESA, S n ← S 1 transition) of the compound. , With the increase of delay time, at 900 fs, the negative band at 630 nm shifted to the blue region (600 nm) consistent with the ground-state bleaching (GSB) of the absorption spectra of ABSQ-H , whereas the negative transient absorption band at 730 nm evolved to attain the steady-state emission maximum at 740 nm, corresponding to the stimulated emission (SE). In addition, a formation of peak at around 680 nm was observed.…”
Section: Resultsmentioning
confidence: 96%
“…However, in the bulk heterojunction-based photovoltaic and photodetector devices using phenyl-C 61 -butyric acid methyl ester (PCBM, an electron acceptor), the ultrafast processes of photoinduced charge transfer, charge carrier generation, and their recombination control the efficiency of the devices. Though a large number of steady-state and time-resolved photophysical properties of squaraine derivatives were widely reported, the intermolecular interaction dynamics of unsymmetrical squaraine derivatives with PCBM have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Squaraine derivatives are another promising class of molecules which show excellent photochemical and thermal stability, and also benefit from a narrow absorption band in the visible and in the NIR region (Beverina and Salice, 2010). Owing to their simple synthesis and good environmental stability, squaraine dyes have been successfully used in a number of technologically relevant applications such as dye-sensitized solar cells (Alagumalai et al, 2016), field-effect transistors (Maeda et al, 2018), photovoltaic cells (Chen et al, 2017a), photodetectors (Strassel et al, 2018), nonlinear optics, or bioimaging (Chang et al, 2019). In particular, Stender et al reported an EL peaked at 550 and 730 nm with EQE up to 0.65% from LEDs incorporating a bromoindolenine squaraine dye into poly(phenylenevinylene) (Stender et al, 2013).…”
Section: Other Classes Of Nir Emittersmentioning
confidence: 99%
“…Squaraine dyes show intense near-IR absorption and emission and strong nonlinear response, which make them ideal candidates for photonic materials in several potential applications. Furthermore, owing to the rather simple synthetic access of a great variety of monomeric, oligomeric, and polymeric squaraine dyes, there are extensive possibilities to design a range of superchromophores with tuneable optical properties. Therefore, these organic dyes play an important role in diverse applications such as imaging, nonlinear optics, biological labeling, and more. In particular, fluorescent dyes that can be excited by the simultaneous absorption of two near infrared (NIR) photons are highly sought after for bioimaging because biological tissue is transparent in the NIR and scattering is strongly reduced for photons with long wavelengths. , Another nonlinear optical application that has attracted much interest is optical power limiting of NIR photons for protection of human eyes or optical sensors from intense laser irradiation, optical pulse processing, or laser mode locking. It is a prerequisite for such applications that the material possesses a high transmission of low intensity near-IR light and a high extinction coefficient at high intensities, greater than an optical limiting threshold. Thus, one of the requirements for optical limiting applications is a high two-photon absorption (2PA) probability at the wavelength of interest.…”
Section: Introductionmentioning
confidence: 99%